2014
DOI: 10.2113/gssgfbull.185.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Orbitally-induced changes of the Atlantic and Indian monsoons over the past 20,000 years: New insights based on the comparison of continental and marine records

Abstract: International audienceVariations of Atlantic and Indian monsoon systems since the last glacial period are investigated by comparing eolian fluxes from two marine cores (ODP site 658 off western Africa and core 74KL off the Arabian peninsula) with 2147 hydrological records (lacustrine, palustrine, spring and fluvial, arid) gathered over a large continental area extending between 10 and 30oN across Africa, Arabia and western India. We show that the hydrological response to the Holocene humid phase in the norther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 61 publications
5
30
0
Order By: Relevance
“…But the end of the HHP, on the other hand, was rather progressive (Foerster et al, 2012), suggesting a climatic transition that was gradual, confirming what has been deduced from lacustrine sediments in the Sahara desert (Kröpelin et al, 2008). Lézine et al (2014) stressed out regional differences in the dynamics of HHP onset and termination based on a comprehensive dataset of nearly 2147 well-dated hydrological records (lacustrine, palustrine, spring and fluvial, arid). They showed that the Arabian Peninsula and the Horn of Africa have experienced a significantly shorter humid period compared to northern Africa even though the optimum of the Holocene humiditywas contemporaneous.…”
Section: Accepted Manuscriptsupporting
confidence: 76%
See 4 more Smart Citations
“…But the end of the HHP, on the other hand, was rather progressive (Foerster et al, 2012), suggesting a climatic transition that was gradual, confirming what has been deduced from lacustrine sediments in the Sahara desert (Kröpelin et al, 2008). Lézine et al (2014) stressed out regional differences in the dynamics of HHP onset and termination based on a comprehensive dataset of nearly 2147 well-dated hydrological records (lacustrine, palustrine, spring and fluvial, arid). They showed that the Arabian Peninsula and the Horn of Africa have experienced a significantly shorter humid period compared to northern Africa even though the optimum of the Holocene humiditywas contemporaneous.…”
Section: Accepted Manuscriptsupporting
confidence: 76%
“…Foerster et al, 2012;Tierney and deMenocal, 2013; Figure 6E) and speleothems from Socotra (Shakun et al, 2007;Van Rampelbergh et al, 2013) which date the onset of the post glacial humidity increase from 14.68-14.5 ka ( Figure 6D). Such an early increase in humidity is also evidenced in the development of lakes and wetlands over the Horn of Africa (Lézine et al, 2010(Lézine et al, , 2014; Figure 6F), although the signal remains weak.The trend of humidityin the pollen record from core MD92-1002 was punctuated by two phases of return to dryer conditions: at 12.7ka, then at 10.4ka, in phase with periods of enhanced wind activity of N-S direction responsible for dust…”
Section: Local Hydrology and Relations With The Surrounding Land Massesmentioning
confidence: 65%
See 3 more Smart Citations